2015
DOI: 10.1017/s002081831400040x
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gap: State Capacity and the Implementation of Human Rights Treaties

Abstract: According to recent studies, international human rights treaties are inef-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(81 citation statements)
references
References 98 publications
0
81
0
Order By: Relevance
“…A different influential line of argument privileges the domestic arena, focusing on the notion of national institutional capacity as the primary determinant of compliance with international human rights rules and norms. Studies have found national compliance to be positively correlated with stronger and more efficient national bureaucracies, although no association has been found between levels of compliance and levels of national economic development (see, e.g., Cole 2016Cole , 2015Anagnostou and Mungiu-Pippidi 2014;Hillebrecht 2014b). At the same time, the thesis that non-compliance is often inadvertent and conditioned by a state's ability to implement pertinent rules and norms (Cole 2015) has chimed with the rise of 'co-operative' approaches to compliance within Europe, which have seen political and policy elites advocating technical assistance and supportive language -rather than naming and shamingas the most appropriate means of dealing with non-compliance (Smith 2015).…”
Section: Sappho Xenakis and Leonidas K Cheliotismentioning
confidence: 99%
See 1 more Smart Citation
“…A different influential line of argument privileges the domestic arena, focusing on the notion of national institutional capacity as the primary determinant of compliance with international human rights rules and norms. Studies have found national compliance to be positively correlated with stronger and more efficient national bureaucracies, although no association has been found between levels of compliance and levels of national economic development (see, e.g., Cole 2016Cole , 2015Anagnostou and Mungiu-Pippidi 2014;Hillebrecht 2014b). At the same time, the thesis that non-compliance is often inadvertent and conditioned by a state's ability to implement pertinent rules and norms (Cole 2015) has chimed with the rise of 'co-operative' approaches to compliance within Europe, which have seen political and policy elites advocating technical assistance and supportive language -rather than naming and shamingas the most appropriate means of dealing with non-compliance (Smith 2015).…”
Section: Sappho Xenakis and Leonidas K Cheliotismentioning
confidence: 99%
“…Studies have found national compliance to be positively correlated with stronger and more efficient national bureaucracies, although no association has been found between levels of compliance and levels of national economic development (see, e.g., Cole 2016Cole , 2015Anagnostou and Mungiu-Pippidi 2014;Hillebrecht 2014b). At the same time, the thesis that non-compliance is often inadvertent and conditioned by a state's ability to implement pertinent rules and norms (Cole 2015) has chimed with the rise of 'co-operative' approaches to compliance within Europe, which have seen political and policy elites advocating technical assistance and supportive language -rather than naming and shamingas the most appropriate means of dealing with non-compliance (Smith 2015). Interpreted in this way, however, the privileging of domestic capacity as an explanans of differential compliance has given rise to concerns that states that do not comply are thereby effectively exculpated, when -as human rights NGOs have pointed out -violations are often the outcome of deliberate state policy, rather than of a state's failure to act or lack of capacity to protect (ibid.…”
Section: Sappho Xenakis and Leonidas K Cheliotismentioning
confidence: 99%
“…Others focus on the role of domestic level factors. Since many international agreements are not self-enforcing, threaten limited international costs for non-adherence, and empirical evidence suggests that most states follow through with their international commitments most of the time, some argue that a lack of capacity at the domestic level impedes states' ability to follow through with their commitments (Chayes and Chayes 1998;Mitchell 1994;Weiss and Jacobson 2000;Simmons 2002;Tallberg 2002;Cole 2015;Gray 2014). From this perspective, states generally want to abide by their commitments, but doing so often requires legal, bureaucratic, economic, or other specialized expertise, not to mention absolute political control, that many states lack.…”
Section: Why States Abide By Institutional Commitments (Or Not)mentioning
confidence: 99%
“…FRANCK, T.M., The Power of Legitimacy Among Nations, Oxford University Press, 1990;GUZMAN, A., How International Law Works: A Rational Choice Theory, Oxford University Press, 2008, pp. 33-71;COLE, W. (2015), Mind the Gap: State Capacity and the Implementation of Human Rights Treaties. International Organization 69 (2): 405-41; GOLDSMITH, J., and POSNER, E. (2005), The Limits of international human rights obligations is due to various factors, including the specific nature of international human rights law, the quality of the judges and the judgments, and the problems related to giving effect to the judgments.…”
Section: The Reasons Behind Non-compliance With the Conventionmentioning
confidence: 99%